MICROSPECTROPHOTOMETRIC QUANTIFICATION OF THE SKELETAL MUSCLE GLYCOGEN CONTENTS WITH AGING (Iraqi Journal of Medical Sciences, 2016)
Background:Skeletal muscle fibers contain about 2% of its weight is glycogen, this glycogen used to keep the muscle functioning if it fails to receive sufficient oxygen. PAS stain is useful in detecting cytoplasmic accumulation of glycogen. Glycogen had been studied in skeletal muscles under various state of muscle activities and nutritional states but glycogen quantification with aging is not clearly defined till now.Objectives:Quantification of the mean glycogen concentration in skeletal muscles fibers stained with PAS stain in various age groups by microspectrophotometry.Methods:The tibialis anterior muscle of 20 Albino male rats (rattus rattus norvegious) of neonate, 3, 6, 9, 12, and 18- months were selected. Paraffin blocks were performed, sectioned and stained with PAS stain.Analysis of the PAS stained sections by microspectrophotometry at 510 nm wave length. For the test group, mean absorbance, standard deviation, maximum, minimum, and mode values were estimated and compared with the control groups.Results:A significant difference in PAS absorbtion between test and control groups, and among different age groups, being increased with age.Conclusion:The variation in PAS absorbtion with aging indicates that the glycogen content in skeletal muscle increase with aging, this could be due to the influence of age on skeletal muscle glucose transport and glycogen metabolism.Key words:Skeletal muscle, PAS, Glycogen, Microspectrophotometry
Keywords: Skeletal muscle; PAS; Glycogen; Microspectrophotometry